VD_FINDINFO HC / 2011 / 366 vom 24. Juni 2011 - VD Tribunal cantonal (2011)
VISITE, RELATIONS PERSONNELLES, MESURE D'ÉLOIGNEMENTEN GÉNÉRAL, VIOLENCE DOMESTIQUE, MENACEEN GÉNÉRAL | 172 CC, 176 al. 3 CC, 273 CC, 274 al. 2 CC, 28b al. 2 CC, 308 CPC (CH), 310 CPC (CH), 314 al. 1 CPC (CH)